Are biomass partitioning and nutrient accumulation in industrial tomato influenced by NPK fertilization? - Almeida Neta, Maria Nilfa; da Mota, Wagner Ferreira; Pegoraro, Rodinei Facco; Batista, Caik Marques; Silva, Aderson Rogerio Soares; Silva, Polyana Danyelle dos Santos; Pacheco, Maricelia Costa (Comunicata Scientiae, 2021)
This study aimed to evaluate the uptake, accumulation, and partitioning of nitrogen (N), phosphorus (P), and potassium (K) in the tomato crop fertilized with doses of NPK. The main plots consisted of three doses of N: 90, 135, and 180 kg ha-1, P: 270, 405, and 540 kg ha-1, and K: 225, 337, and 450 kg ha-1 (equivalent to 50, 75, and 100 % of the fertilization recommendation for industrial tomato), while the subplots consisted of the evaluation periods: 20, 40, 60, 80, and 100 days after transplanting (DAT). The dry matter and the accumulation of N, P, and K were characterized in the different plant components (leaves, stems, fruits, and total). The order of nutrient uptake for the hybrid BRS Sena was defined as K> N> P. The dose corresponding to 50 % NPK resulted in the maximum accumulation of total dry matter of 400 g per plant at 64 DAT and the total accumulation of 10, 1.14, and 14.51 g per plant of N, P, and K, respectively. The intermediate dose of NPK resulted in the maximum accumulation of total dry matter of 468 g and accumulations of 14, 1.6, and 19 g per plant of N, P, and K. At 100 % of the NPK recommendation, there was 514 g per plant of total dry matter, with maximum accumulations of 15, 1.6, and 18 g per plant of N, P, and K. The maximum accumulation rate of N, P, and K occurs at 60, 64, and 70 DAT for the fertilization recommendations corresponding to 50, 75, and 100 % NPK, respectively.